Low analysis of community interest maintenance in Central Health Center Sukmajaya Kota Depok Provinsi Jawa Barat - Gabe Gusmi Aprilla (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2020)
According to the recapitulation of the utilization of Community Health Center inpatient services in Depok in 2016-2018, it was very low. The results of an initial survey in October 2018 conducted by Community Heath Center researchers who only served inpatients in only 3 districts, while 1 sub-district had not served general inpatients since one year ago. Of the three sub-districts, only 1 sub-district has inpatients, while others sometimes do not have an in-patient visit within one month. Sukmajaya Community Health Center was appointed to serve general inpatient care, basic neonatal obstetric services and care for malnourished children. Because of the low number of inpatient visits in the city of Depok, the researchers were interested in knowing the strengths and weaknesses as well as the opportunities and threats of the Sukmajaya Community Health Center. This study used a qualitative method conducted in February 2020 with in-depth interviews using interview guidelines and voice recording devices. Interviews were conducted with the Head of the Community Health Center, Head of Administration, Responsible for Inpatients, Doctors and Nurses. As a result, Sukmajaya Community Health Center was unable to compete with Private Hospitals because private hospitals had better health personnel and infrastructure than Sukmajaya Community Health Center. Besides that, the number of private hospitals in the city of Depok is large and the location is easy to reach, so people prefer hospitals with more convenient facilities.